Optimal Operational Profiles in an Electrodialysis Unit for Ion Recovery - Athanasios Latinis (AIDIC Servizi S.r.l., 2021)
Electrodialysis is an efficient process for the cleaning of industrial water effluent streams from toxic ionic substances with the simultaneous recovery of valuable ions for reuse. Energy consumption and waste recovery are the two key goals of the process. A dynamic optimisation program aims to determine the optimal operating conditions in terms of applied voltage and effluent flow rate in a batch operating scheme. A model is developed that accounts for the ion transfer through the ion selective membranes and the dynamics of the system. A combination of three objective functions targeting the minimisation of the overall batch process time, the minimisation of the electrical energy consumption required for the ion transfer, and the maximisation of the overall degree of separation is investigated. The manipulated variables applied voltage and feed stream flow rate are considered as piecewise constant during each time interval, spanning the duration of the entire batch. The dynamic optimisation problem is solved through standard non-linear programming techniques which calculate the optimal batch duration and condition profiles for the system. A multi-objective analysis is presented for various combinations of weight values for the joint objective function through the development of the Pareto optimal front. The current approach has been implemented in the removal and recovery of sulfuric anions from an aqueous solution and resulted in the achievement of a high degree of separation in a shorter period at a much lower energy consumption.